A Combined Experimental and Theoretical Study on the Formation of a Cyclic Tetrameric Water Cluster and a Similar Type of Cyclic Cluster in Copper(II) Schiff Base Complexes. Issue 29 (12th October 2017) - Roy, Sourav; Basak, Tanmoy; Khan, Samim; Drew, Michael G. B.; Bauzá, Antonio; Frontera, Antonio; Chattopadhyay, Shouvik
Abstract: Two copper(II) complexes, [CuL 1 ]⋅2H2 O (1 ) and [CuL 2 ]⋅H2 O (2 ) [where H2 L 1 = N, N′‐bis(3‐methoxysalicylidene)propane‐1, 3‐diamine and H2 L 2 =N, N′‐bis(3‐ethoxysalicylidene)propane‐1, 3‐diamine are potential hexadentate N2 O4 donor compartmental Schiff bases], were synthesized and characterized. In each complex, copper(II) was placed in the inner N2 O2 environment, with a four‐coordinate distorted square planar environment keeping the outer O4 compartment pendant. Lattice water molecules were hydrogen bonded with the pendant O4 compartments of the Schiff base ligands. Both complexes formed self‐assembled dimers via chelate ring⋅⋅⋅chelate ring and C–H⋅⋅⋅π interactions. A cyclic tetrameric water cluster was stabilized by the oxygen rich region of the Schiff‐base ligand in complex1 . A similar type of cyclic cluster involving two water molecules was also observed in complex2 . These supramolecular assemblies were analysed via a DFT study at the M06‐2X/def2‐TZVP level of theory. Abstract : Two Schiff base copper(II) complexes [CuL 1 ]⋅2H2 O (1 ) and [CuL 2 ]⋅H2 O (2 ) [where H2 L 1 = N, N′‐bis(3‐methoxysalicylidene)propane‐1, 3‐diamine and H2 L 2 =N, N′‐bis(3‐ethoxysalicylidene)propane‐1, 3‐diamine] were synthesized and characterized. A cyclic tetrameric water cluster was formed by hydrogen bonding interaction in complex1 whereas a dimeric centrosymmetric (alkyl supported) water cluster involving two water molecules was observed in complex 2. DFT study was performed to analyze the formation of self‐assembled dimers via supramolecular interactions.